2002
DOI: 10.2298/hel0236177b
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic variability for sclerotinia sclerotiorum (Lib) de Bary resistance in sunflower and utilization of associated molecular markers

Abstract: In the framework of a bilateral project Italy -Romania (University of Udine and IC), an experiment was established at the University of Udine Experiment Station in order to: i) evaluate the genetic variability of the tested genotypes for Sclerotinia basal stem and head infection; ii) to test two new alternative screening methods against white head rot; iii) to investigate possible relationships among the different tests; iiii) to find resistance-associated fragments by AFLP analysis.The following tests were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Possibly, solutions that are more concentrated would be required, in contrast to what was recommended for common beans and soybeans (KOLKMAN;KELLY, 2000;ANTÔNIO et al, 2008;HÜLLER et al, 2016;SOUZA et al, 2016). The inconsistency of the oxalic acid method discourages the indirect evaluation of cotton resistance to white mold, be it by need to optimize the technique or by the combination with other physiological mechanisms of resistance in cotton, such as biosynthesis of phytoalexins, shikimic acid, phenolic compounds or oxalate detoxification (BALDINI et al, 2002;CUNHA et al, 2010;DAVIDSON et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possibly, solutions that are more concentrated would be required, in contrast to what was recommended for common beans and soybeans (KOLKMAN;KELLY, 2000;ANTÔNIO et al, 2008;HÜLLER et al, 2016;SOUZA et al, 2016). The inconsistency of the oxalic acid method discourages the indirect evaluation of cotton resistance to white mold, be it by need to optimize the technique or by the combination with other physiological mechanisms of resistance in cotton, such as biosynthesis of phytoalexins, shikimic acid, phenolic compounds or oxalate detoxification (BALDINI et al, 2002;CUNHA et al, 2010;DAVIDSON et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There are proteomics, metabolomics and transcriptomics reports of the interactions Sclerotinia-Glycine max (L.) Merrill, Sclerotinia-Phaseolus vulgaris L., Sclerotinia-Helianthus annuus L. and Sclerotinia-Brassica napus L. (PELUFFO et al, 2010;GARG et al, 2013;OLIVEIRA et al, 2015;CAO;XU;CAI, 2016;JOSHI et al, 2016a;WU et al, 2016). Even the selection of genes and genotypes resistant to the fungus overlook cotton while including alfalfa (PRATT; ROWE, 1991), peanut (AKEM; MELOUK; SMITH, 1992), sunflower (ACHBANI;DE LABROUHE;VEAR, 1994;BALDINI et al, 2002;DAVAR et al, 2011), lentil (AKEM; BELLAR; BAYAA, 2006), peas (PORTER; HOHEISEL; COFFMAN, 2009), okra (FISCHER et al, 2014), canola (AHMADIFAR;DALIL, 2013;WU et al, 2013;JOSHI et al, 2016b), common beans (LEITE, 2014;ABREU, 2016) and soybeans (GARCIA;JULIATTI, 2012;BASTIEN;SONAH;BELZILE, 2014;JULIATTI et al, 2014;IQUIRA;HUMIRA;FRANÇOIS, 2015;CASTRO et al, 2016;WEI et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Using four different tests for the evaluation of Sclerotinia resistance (basal stem infection, ascospore, and oxalic acid injection into the back face of the head), Baldini et al [72] found that the inbred line 28R was most tolerant to the basal stem and white head rot infections and it also showed the best performance in oxalate and culture filtrate tests, which indicated the presence of a specific resistance to oxalate.…”
Section: White Rot [Sclerotinia Sclerotiorum (Lib) De Bary]mentioning
confidence: 99%
“…Research involving the heads of infected plants has shown that tolerance to white rot is related to the accumulation of phenolic (Prats et al 2003) and coumarin compounds (Prats et al 2006) and to the absence of the phytotoxic effect of oxalic acid (Baldini et al 2002). Oxalic acid concentration increases when tissues are damaged and this can be used as an indirect method for selecting on the basis of tolerance to disease (Vasic et al 2002).…”
Section: Disease Controlmentioning
confidence: 99%